Skin Cancer Awareness Among 1 271 Black Africans in South Africa. (19th February 2020) - Wright, Caradee Y.; Wallace, Melissa; Mistri, Preethi; Wernecke, Bianca; Kapwata, Thandi
Abstract: Little is known about levels of awareness and perceptions of skin cancer among Africans living in Africa. This study assessed skin cancer awareness among 1271 deeply pigmented South Africans. Participants ( n  = 642 males vs n  = 629 females) were aware of skin cancer (79%) with more females than males being aware of skin cancer ( P  = 0.02). Majority of all participants had never checked their skin for signs or symptoms of skin cancer (90%). Palms of hands and soles of feet were the least recognized anatomic sites for skin cancer development, despite these sites being the common sites for acral lentiginous melanoma in individuals with deeply pigmented skin. Results suggest a need for targeted skin cancer awareness among population groups with dark skin on identification, screening, and early detection, professional training for healthcare personnel and content on skin cancer in deeply pigmented skin in medical curricula. Abstract : We interviewed 1271 participants with deeply pigmented skin. Ninety percent of all participants had never checked their skin for signs or symptoms of skin cancer. Palms of hands and soles of feet were the least recognised sites for skin cancer development despite these anatomic sites being most common for the development of acral lentiginous melanoma in people with deeply pigmented skin. While it is known that skin cancer can affect Black Africans on anatomic sites never exposed to sunlight, our results suggest a need for targeted skin cancer awareness on identification, screening and early detection.